e-Learning using the study companion approach for secondary school mathematics (ESCA-Math) / Nur Azizan @ Nur Azyan Yusof - Nur Azizan @ Nur Azyan, Yusof (2008)
In schools educational system, the advancing technologies in e-learning should not focus on the transition from conventional classroom teaching to self-pursue e-learning system, but instead how these technologies can be used to support the learning process. However, without careful considerations, students fail to acknowledge and benefit from the support systems and causes low level of satisfaction towards using them. The main objective of this study is to investigate and suggest solutions to the problems that resulted in low to moderate percentage of satisfaction in the usage of Internet and e-learning system towards educational pursuit among students. The results of the questionnaire analysis gives an insight on the problems which include the lack of time, lack of attention provided by the existing system and the lack for self-assessment. ESCA-Math which is a prototype that was developed based on the framework formulated from the analysis stage is a suggestion to address these problems using the study companion approach. In this approach, there will be no teacher presence, but the interaction between the system and the user alone. This way, students are able to carry out their learning process without any outside pressure, thus highlight on the meaning of the study companion. It emphasize on its ability to track students’ progress and provide topics assessment scheme to guide students with their learning process. There is also an administrator account feature to allow future maintenance and addition to the content of the system in order to keep track with the changes by the educational system. To ensure ESCA-Math prototype is developed efficiently and effectively, the system model adapts from the waterfall model with prototyping to cover all aspect in system development life cycle. In the user acceptance testing, it shows that students are mostly satisfied with ESCA-Math and believe that it will benefit them as their